NGUYEN CONG TRU’S THOUGHTS IN YONGSHI POETRY THEMES - Nguyễn Cảnh Chương (Tạp chí Khoa học Đại học Đà Lạt)
Nguyen Cong Tru (1778 - 1858) was brilliant both as a poet and a great personality of Vietnam in the early nineteenth century. His social status, career and especially the complexity and diversity in his thoughts about literature are the origin of contradictory critics and evaluation, which are still a concern to the contemporary academic community and to all those who are interested in those thoughts. Based on the analysis and comparative methods, this article is an attempt to discover Nguyen Cong Tru’s thoughts in yongshi poetry themes.